Studi Tingkat Kepuasan Terhadap Pelayanan Travel Rute Palangka Raya-Buntok - Rin; Devia; Murniati (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Palangka Raya City as the growth center of Central Kalimantan and surrounding areas needs transportation facilities that can support the economy of the people. This study aims to evaluate the level of passenger satisfaction that has been achieved and identify which indicators need immediate improvement by applying the Customer Satisfaction Index (CSI) method, the Importance Performance Analysis (IPA) method and the Service Quality method. The results of the CSI analysis produce a value of 63.88%, meaning that the overall level of travel service on the Palangka Raya-Buntok route is quite satisfactory and the results of the Cartesian diagram from the IPA analysis of the indicators that fall into quadrant I are that the travel driver is in good physical and mental health and does not smoke or play on his cellphone. while driving, the car room is smoke-free, and transactions and services are served quickly and precisely, quadrant I is considered very important, but performance is not optimal so, improving it is a top priority, a strategy that can be carried out by the authorities by providing direction to drivers and bureau employees travel journey regarding matters relatedto these indicators.